2018
DOI: 10.3389/fphar.2018.00155
|View full text |Cite
|
Sign up to set email alerts
|

Liposome-Encapsulated Baicalein Suppressed Lipogenesis and Extracellular Matrix Formation in Hs68 Human Dermal Fibroblasts

Abstract: The dermis of human skin contains large numbers of fibroblasts that are responsible for the production of the extracellular matrix (ECM) that supporting skin integrity, elasticity and wound healing. Previously, an in vivo study demonstrated that dermal fibroblasts siting in the lower dermis are capable to convert into skin adipose layer and hence fibroblast lipogenesis may vary the structure and elasticity of dermis. In the present study, Hs68 human dermal fibroblasts were utilized as an in vitro model to stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…However, this group did not provide detailed size distribution graphs or PDI distribution values. Unfortunately, there are no data from this work about the EE% of BAI [ 60 ]. Another BAI loading procedure was reported by Fang et al [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, this group did not provide detailed size distribution graphs or PDI distribution values. Unfortunately, there are no data from this work about the EE% of BAI [ 60 ]. Another BAI loading procedure was reported by Fang et al [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the characterization of the 5,6,7-trihydroxyflavone (baicalein) NPs, it has been found that the size of mesoporous silica NPs (MSNs) is considerably larger, 367 ± 94 nm [ 95 ], than the size of liposomes 135–154 nm [ 96 ] or NPs 82.5 ± 1.7 nm [ 97 ]. Regarding the variation of the size of NPs in the NP population that is PDI, it is observed that nanoemulsions (NE) and NPs are monodisperse, while liposomes vary in size.…”
Section: Nps—flavonesmentioning
confidence: 99%
“…The presence of baicalein does not alter the electrophoretic mobility of the liposomes. Fang et al (2018) [ 96 ] concluded that the reduction in particle size may be mainly due to strong interactions with baicalein via the H-bond but has no effect on the zeta potential.…”
Section: Nps—flavonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids have been proven in studies to lower TGF-β1 and IL-1β production, limit extracellular matrix (ECM) secretion, and prevent excessive fibrous connective tissue deposition ( 97 ). For example, while maintaining the viability of fibroblasts, safranin inhibits TNF-α expression, reduces ECM protein synthesis and improves wound healing ( 98 ). Pinocembrin, the most abundant flavonoid compound in propolis, has anti-fibrotic properties, inhibiting TGF-β1 signaling and impairing TGF-β1-induced proliferation and activation of abnormal skin fibroblasts, effectively alleviating bleomycin (an antibiotic)-induced excessive skin fibrosis ( 99 ).…”
Section: Effect Of Flavonoids To Promote Scar-free Regenerationmentioning
confidence: 99%